A fraction becomes 1, if we add 1 to the numerator and subtract 1 from the denominator. It becomes 1/2 if we only add 1 to the denomi

Question

A fraction becomes 1, if we add 1 to the numerator and subtract 1 from the denominator.
It becomes 1/2 if we only add 1 to the denominator. What is the fraction? Guys pls send it fast

in progress 0
Abigail 3 weeks 2021-10-04T02:11:59+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-10-04T02:13:21+00:00

    GIVEN :-

    • A fraction becomes 1, if we add 1 to the numerator and subtract 1 from the denominator.
    • It becomes 1/2 if we only add 1 to the denominator.

    TO FIND :-

    The fraction.

    PRE-REQUISITE :-

    Let the numerator of the fraction be x and the denominator be y.

    SOLUTION :-

    Case-I

    \sf{\dfrac{x+1}{y-1}=1 }

    \sf{\implies x+1=y-1}\\\\\sf{\implies x-y+2=0}\:\:\:\:\:\:\:\: \cdots(i)

    \rule{160}{2}

    Case-II

    \sf{\dfrac{x}{y+1}=\dfrac{1}{2} }

    \sf{\implies y+1=2x}\\\\\sf{\implies 2x-y-1=0}\:\:\:\:\:\:\:\: \cdots(ii)

    \rule{160}{2}

    Subtracting eq.(i) from eq.(ii) :-

    \sf{\:\:2x-y-1=0}\\-\\\sf{\:\:x-y+2=0}\\\rule{60}{1}\\\sf{\:\:x-3=0}

    \boxed{\sf{\implies x=3}}

    \rule{160}{2}

    Putting the value of x in eq.(i) :-

    \sf{x-y+2=0}\\\\\sf{\implies 3+2=y}\\\\\boxed{\sf{\implies y=5}}

    Therefore, the fraction is 3/5.

  1. Charlotte
    0
    2021-10-04T02:13:24+00:00

    Answer:

    Step-by-step explanation:

    Given :-

    If we add 1 to numerator, and subtract 1 from the denomination, a fraction reduce the 1.

    It becomes ½ if we only add 1 to the denominator.

    To Find :-

    The Fraction

    Solution :-

    Let the fraction be x/y                  

    According to the question,

    ⇒ x + 1/y – 1 = 1                  

    ⇒ x – y = – 2 … (i)

    ⇒ x/y + 1 = 1/2                  

    2x – y = 1 … (ii)             

    Subtracting equation (i) from equation (ii), we get                  

    x = 3 … (iii)              

    Putting this value in equation (i), we get                  

    ⇒ 3 – y = – 2                  

    ⇒ -y =  5                  

    y = 5                  

    Hence, the fraction is 3/5

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )